Hubungan Pengetahuan dan Persepsi dengan Sikap Mahasiswa tentang Alat Kontrasepsi IUD - Wardani, Suci Fitriana Pramudya; Ismiyati, Inayah (JURNAL KESEHATAN TERAPAN, 2024)
Background: Lack of understanding of IUD contraceptives can affect the choice of IUD contraceptives. As women's knowledge decreases, the use of contraceptives, especially IUDs, will also decrease. There is a myth that states that IUDs can affect the comfort of sexual intercourse, misunderstandings and subjective views can cause some people to still be unfamiliar with using IUDs as contraceptives. If women are equipped with knowledge about IUD contraceptives, the awareness to use them will be higher, so that the low interest of the mother will be smaller.. This research was carried out with the aim of finding out "The relationship between knowledge and perception and the attitudes of students at the Brebes College of Health Sciences regarding the IUD contraceptive device in 2023." Method: The type used in this research was an analytical survey with a total research sample of 48 samples conducted at STIKes Brebes. The research instrument used in this study was a questionnaire with a list of questions about knowledge, attitudes and perceptions of IUD contraception given by respondents. then data processing using chi-square statistical test analysis data. Results: The results of statistical tests between knowledge and respondents' attitudes, obtained results of p<0.05, the results of statistical tests between perceptions and attitudes of respondents obtained results of p>0.05) Conclusion: There is a relationship between attitudes and IUD knowledge at STIKES Brebes in 2023 and There is no relationship between attitudes and perceptions of IUDs at STIKES Brebes in 2023. The role of health workers in providing information is very necessary in order to increase knowledge about IUD contraceptives